2015
DOI: 10.4028/www.scientific.net/amm.741.183
|View full text |Cite
|
Sign up to set email alerts
|

Failure Prediction and Wear State Evaluation of Power Shift Steering Transmission

Abstract: Within the vehicle transmission, the friction surfaces of mechanical parts were consecutively worn-out and ultimately up to the degradation failures. For assessing the wear progress effectively, wear particles should be generally monitored by measuring the element concentration through Atomic emission (AE) spectroscopy. Herein, the spectral data sampled from life-cycle test has been processed by both the Principal Component Analysis (PCA) and further Kernel Principal Component Analysis (KPCA). Results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A preliminary analysis indicated that it is sufficient to consider 15 out of 21 elements for PSST degradation modelling and lubrication oil, and we call them wear degradation indicator elements. 14 The oil spectrometric data for one of three PSSTs are shown in Table 2.…”
Section: Degradation Index Constructionmentioning
confidence: 99%
“…A preliminary analysis indicated that it is sufficient to consider 15 out of 21 elements for PSST degradation modelling and lubrication oil, and we call them wear degradation indicator elements. 14 The oil spectrometric data for one of three PSSTs are shown in Table 2.…”
Section: Degradation Index Constructionmentioning
confidence: 99%